1988
DOI: 10.1007/bf00027391
|View full text |Cite
|
Sign up to set email alerts
|

Plastid and nuclear mRNA fluctuations in tomato leaves ? diurnal and circadian rhythms during extended dark and light periods

Abstract: Steady-state mRNA levels of nuclear (rbcS, cab, tubA) and plastid (rbcL, psbA) encoded genes were determined in tomato leaves of different developmental stages. Transcripts were analyzed at four-hour intervals throughout a diurnal cycle in 4 cm-long terminal leaflets, while mRNA levels of the chlorophyll a/b-binding protein (cab), and the small and large subunit of RuBPC/Oase (rbcS, rbcL) are high. At different time points during the day the mRNAs accumulate to characteristic levels. Minor fluctuations of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 22 publications
4
44
0
2
Order By: Relevance
“…The outlying peak during the continuous dark period may be an anomally. However, erratic fluctuations and somewhat higher levels of psbA expression during dark phases have also been found in tomato (16 (19). Our study showed that diurnal fluctuations of the steady-state cab mRNA in Douglas-fir were relatively minor and the fluctuations that occurred did not appear to be highly influenced by factors associated with photoperiodicity.…”
Section: Expression Of Cab and Psba Genes In Douglas-firsupporting
confidence: 60%
“…The outlying peak during the continuous dark period may be an anomally. However, erratic fluctuations and somewhat higher levels of psbA expression during dark phases have also been found in tomato (16 (19). Our study showed that diurnal fluctuations of the steady-state cab mRNA in Douglas-fir were relatively minor and the fluctuations that occurred did not appear to be highly influenced by factors associated with photoperiodicity.…”
Section: Expression Of Cab and Psba Genes In Douglas-firsupporting
confidence: 60%
“…To provide a comparison with a gene of known function, we identified the P. nil Cab gene as a well-characterized gene known to be regulated by light and an endogenous rhythm (Piechulla, 1988;Meyer et al, 1989;Millar and Kay, 1991 O'Neilletal. Plant Physiol.…”
Section: Dark-and Circadian-regulated Transcriptsmentioning
confidence: 99%
“…The involvement of circadian rhythms in light-regulated gene expression of plants is widely recognized (Kloppstech, 1985;Guilano et al, 1988;Nagy et al, 1988;Piechulla, 1988;Meyer et al, 1989;Millar and Kay, 1991). In the majority of studies of circadian-regulated gene expression in plants, light rather than darkness is the extemal signal influencing the amplitude of cycling mRNA levels (Guilano et al, 1988;Taylor, 1989).…”
Section: Ldentification Of Mrnas Associated With Photoperiodicmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the rbcS gene, Lhc genes were the first to be cloned (Broglie et al, 1981) and were used in some of the first gene expression studies. Lhc gene expression is primarily regulated by the intensity and quality of light on a transcriptional level (for review, see Brunner and Ruediger, 1995), and Lhc mRNA levels are subject to pronounced circadian and diurnal fluctuations (Kloppstech, 1985;Pichulla, 1988). Lhc gene promoters have subsequently also been used in mutant screening experiments to elucidate the different light-sensing pathways in plants (Chory et al, 1995).…”
mentioning
confidence: 99%